AgNPs@CeO2/Nafion Nanocomposite-Modified Electrode for the Sensitive Detection of Trace Lead (II) in Water Samples - Zhengying Guo; Peng Xu; Shiqing Zhou; Ruoxi Wu (Sensors)
Excessive levels of heavy metal pollutants in the environment pose significant threats to human health and ecosystem stability. Consequently, the accurate and rapid detection of heavy metal ions is critically important. A AgNPs@CeO2/Nafion composite was prepared by dispersing nano-ceria (CeO2) in a Nafion solution and incorporating silver nanoparticles (AgNPs). The morphology, microstructure, and electrochemical properties of the modified electrode materials were systematically characterized using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), and cyclic voltammetry (CV). By leveraging the oxygen vacancies and high electron transfer efficiency of CeO2, the strong adsorption capacity of Nafion, and the superior conductivity of AgNPs, an AgNPs@CeO2/Nafion/GCE electrochemical sensor was developed. Under optimized conditions, trace Pb2+ in water was detected using square wave anodic stripping voltammetry (SWASV). The sensor demonstrated a linear response for Pb2+ within the concentration range of 1–100 μg·L−1, with a detection limit of 0.17 μg·L−1 (S/N = 3). When applied to real water samples, the method achieved recovery rates between 93.7% and 110.3%, validating its reliability and practical applicability.